E-Learning Management System - Malathi, M.; Surya, A.; Subha, I.; Prakash, G. (Journal of Neonatal Surgery, 2025)
The LMS aims to provide a seamless and engaging learning environment by offering personalized learning paths, real-time progress monitoring, and interactive assessments. It will cater to students, instructors, and administrators, ensuring and intuitive and scalable solution for educational institutions and corporate training programs. This system enables multi- user authentication, real-time progress tracking, and automated certificate generation. The architecture ensures scalability and security while offering an interactive learning experience. It serves as an essential tool for educators, trainers, and organizations to streamline learning processes efficiently. By leveraging modern technologies, this LMS will enhance learning accessibility, efficiency and engagement making education more structured and effective. This design and development of Learning Management System (LMS) using React.js, Python and MySQL aimed to enhancing student engagement progress monitoring. The proposed LMS is built with Python as a backend, react.js for the frontend, and MySQL for the database management.